2015
DOI: 10.1094/phyto-12-14-0356-rvw
|View full text |Cite
|
Sign up to set email alerts
|

Plant Virus Metagenomics: Advances in Virus Discovery

Abstract: In recent years plant viruses have been detected from many environments, including domestic and wild plants and interfaces between these systems-aquatic sources, feces of various animals, and insects. A variety of methods have been employed to study plant virus biodiversity, including enrichment for virus-like particles or virus-specific RNA or DNA, or the extraction of total nucleic acids, followed by next-generation deep sequencing and bioinformatic analyses. All of the methods have some shortcomings, but ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
256
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 328 publications
(278 citation statements)
references
References 92 publications
1
256
0
7
Order By: Relevance
“…The past ten years have seen the establishment of five new geminivirus genera, and the next ten will likely see many more being established as metagenomics-based approaches begin enabling the convenient and cost-effective discovery of viruses in greater numbers from cultivated and non- Percentage identity Proportion of percentage pairwise identities cultivated plant host species [29,32]. As well as illuminating the actual diversity of geminiviruses and the role played by recombination in their evolutionary history, such approaches also have the potential to elucidate the full range of geminivirus host and vector species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The past ten years have seen the establishment of five new geminivirus genera, and the next ten will likely see many more being established as metagenomics-based approaches begin enabling the convenient and cost-effective discovery of viruses in greater numbers from cultivated and non- Percentage identity Proportion of percentage pairwise identities cultivated plant host species [29,32]. As well as illuminating the actual diversity of geminiviruses and the role played by recombination in their evolutionary history, such approaches also have the potential to elucidate the full range of geminivirus host and vector species.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, the development of new molecular tools such as rolling-circle amplification (RCA) and highthroughput sequencing have greatly facilitated the discovery of novel geminiviruses in a range of cultivated and noncultivated host species [29]. Accordingly, these techniques have accelerated the discovery of highly divergent geminivirus-like viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, next-generation sequencing technology has provided a rapid approach to high-throughput sequence determination and allowed a wide diversity of novel viruses to be discovered (Ansorge, 2009;Mokili et al, 2012;Roossinck et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, other forms of biological pest control, including the use of host-specific viral pesticides, derived from baculovirus (Allaway and Payne, 1984;Chen et al, 2001;Fuxa, 2004;Sun et al, 2002;Sun et al, 2004), small RNA viruses (Christian et al, 2005) and densoviruses (El-Far et al, 2012), has attracted more attention from researchers. Moreover, high-through-put analytical methods such as metagenomics and RNA sequencing provide sensitive and effective methods for the discovery of novel viruses and asymptomatic disease agents that may be useful as biological control products (Diatchenko et al, 1996;Ge et al, 2012;Marguerat and Bähler, 2009;Mokili et al, 2012;Radford et al, 2012;Roossinck et al, 2015), or conversely, may negatively or positively impact upon the biopesticide products being used. For example, the recent discovery of a novel densovirus (HaDV2) from healthy migratory cotton bollworms revealed that HaDV2 infection significantly increased host resistance to the host-specific baculovirus HaNPV and to the generalist biopesticide Bt toxin (Xu et al, 2014).The development of molecular tools and next generation sequencing technology paves the way for a greater understanding as to how we may manipulate the host-pathogen system, with the aim of reducing pest outbreaks and economic crop damage.…”
Section: Introductionmentioning
confidence: 99%
“…Grapevine species and hybrids used as rootstocks are hosts of about 65 viruses, eight viroids and 13 phytoplasmas. This amount increases frequently due to the continuous development of techniques for the detection of these pathogens, especially next generation sequencing (NGS) (MARTELLI, 2014;ROOSSINCK et al, 2015).…”
Section: New Diseases Transmitted By Vegetative Propagationmentioning
confidence: 99%